Near Eastern Alloying and Some Textual Use of Arsenical Copper - Eaton, E. R.
alternative interpretations of AN.NA, annaku, Eg. d'm, όρείχαλϰος: 'high arsenic content copper' or 'arsenic-coated copper'.